2016
DOI: 10.1002/jmor.20617
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and nerve net organization in stalked jellyfish (Medusozoa: Staurozoa)

Abstract: Staurozoan cnidarians display an unusual combination of polyp and medusa characteristics and their morphology may be informative about the evolutionary origin of medusae. We studied neuromuscular morphology of two staurozoans, Haliclystus 'sanjuanensis' and Manania handi, using whole mount immunohistochemistry with antibodies against FMRFamide and α-tubulin to label neurons and phalloidin to label muscles. All muscles appeared to lack striations. Longitudinal interradial muscles are probable homologues of stal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…In many species, these muscles are constituted by myocytes completely embedded in the mesoglea, and thus not connected either to the ectoderm or the endoderm epithelia (Widersten, 1966; Werner et al, 1976; Chapman, 1978; Chia et al, 1984; Westlake and Page, 2016). In addition, smooth epitheliomuscular cells are present in the ectoderm of the polyp tentacles (Franc, 1993).…”
Section: Cnidarian Muscle Typesmentioning
confidence: 99%
“…In many species, these muscles are constituted by myocytes completely embedded in the mesoglea, and thus not connected either to the ectoderm or the endoderm epithelia (Widersten, 1966; Werner et al, 1976; Chapman, 1978; Chia et al, 1984; Westlake and Page, 2016). In addition, smooth epitheliomuscular cells are present in the ectoderm of the polyp tentacles (Franc, 1993).…”
Section: Cnidarian Muscle Typesmentioning
confidence: 99%
“…However, surprisingly we found that all four loci of our M. handi specimen were ≥99.7% identical to M. gwilliami (CA). Since Miranda et al (5) and our study (6), additional COI data from M. gwilliami samples collected in 2018 in Bamfield BC Canada were deposited in GenBank; Bamfield is geographically near our sampling location in Victoria BC Canada. We used this opportunity to confirm these putative identifications of M. handi and M. gwilliami.…”
Section: Resultsmentioning
confidence: 99%
“…We additionally confirmed our specimen as M. handi using characters described in Larson and Fautin (7) Species-level identifications are difficult for lesser-studied marine invertebrates, particularly uncultivable species like staurozoans. By performing an in-depth description in Westlake and Page (6) and generating supporting sequence data (this study), we provide morphological and genetic support for M. handi and M. gwilliami identification efforts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations